The PENGARUH WAKTU PANEN TERHADAP KADAR FLAVONOID TOTAL DAN AKTIVITAS ANTI-INFLAMASI EKSTRAK ETANOL DAUN YAKON (Smallanthus sonchifolius) - Uci Nur Rohmah; Leny Yuanita (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Surabaya State University, located at Jl Ketintang, Surabaya, East Java, Indonesia, 2022)
Yacon (Smallanthus sonchifolius) contains active ingredients in the form of flavonoids. The active ingredients of flavonoids have pharmacological activities such as antimicrobial, anti-inflammatory, and antioxidant. The formation of flavonoids in yacon leaves is influenced by the time of harvest. The study was conducted to determine the effect of harvest time on total flavonoid content and anti-inflammatory activity of ethanol extract of yacon leaf at 4, 6, and 8 months harvest time variations. Yacon leaf extraction process using maceration method. Determination of total flavonoid content in ethanol extract of yacon leaf using a colorimetric method, while testing anti-inflammatory activity using protein denaturation inhibition method. The results showed that harvest time affected total flavonoid content and the anti-inflammatory activity of ethanol extract of yacon leaf. The highest total flavonoid content was obtained at 8 months of harvest, which was 5,366 QE/g. The anti-inflammatory activity of ethanol extract of yacon leaf showed positive results, with an average inhibition value of more than 20% for each harvest time. The best IC50 value is found in yacon leaf with a harvest age of 8 months, which is 29,829 ppm. Keywords: harvest time, flavonoids, anti-inflammatory, yacon leaf